Rideshare-Based Medical Transportation for Medicaid Patients and Primary Care Show Rates: A Difference-in-Difference Analysis of a Pilot Program - Chaiyachati, Krisda H. (J Gen Intern Med, 2018)
BACKGROUND: Transportation to primary care is a well-documented barrier for patients with Medicaid, despite access to non-emergency medical transportation (NEMT) benefits. Rideshare services, which offer greater convenience and lower cost, have been proposed as an NEMT alternative. OBJECTIVE: To evaluate the impact of rideshare-based medical transportation on the proportion of Medicaid patients attending scheduled primary care appointments. DESIGN: In one of two similar practices, all eligible Medicaid patients were offered rideshare-based transportation (“rideshare practice”). A difference-in-difference analytical approach using logistic regression with robust standard errors was employed to compare show rate changes between the rideshare practice and the practice where rideshare was not offered (“control practice”). PARTICIPANTS: Our study population included residents of West Philadelphia who were insured by Medicaid and were established patients at two academic general internal medicine practices located in the same building. INTERVENTION: We designed a rideshare-based transportation pilot intervention. Patients were offered the service during their reminder call 2 days before the appointment, and rides were prescheduled by research staff. Patients then called research staff to schedule their return trip home. MAIN MEASURES: We assessed the effect of offering rideshare-based transportation on appointment show rates by comparing the change in the average show rate for the rideshare practice, from the baseline period to the intervention period, with the change at the control practice. KEY RESULTS: At the control practice, the show rate declined from 60% (146/245) to 51% (34/67). At the rideshare practice, the show rate improved from 54% (72/134) to 68% (41/60). In the adjusted model, controlling for patient demographics and provider type, the odds of showing up for an appointment before and after the intervention increased 2.57 (1.10–6.00) times more in the rideshare practice than in the control practice. CONCLUSIONS: Results of this pilot program suggest that offering a rideshare-based transportation service can increase show rates to primary care for Medicaid patients.